Resuscitation with 100% O2 does not protect the myocardium in hypoxic newborn piglets. Issue 2 (1st March 2004) - Børke, W B; Munkeby, B H; Mørkrid, L; Thaulow, E; Saugstad, O D
Abstract : Background: Perinatal asphyxia is associated with cardiac dysfunction secondary to myocardial ischaemia. Cardiac troponin I (cTnI) is a marker of myocardial necrosis. Raised concentrations in the blood are related to perinatal asphyxia and increased morbidity. Objective: To assess porcine myocardial damage from enzyme release during hypoxaemia induced global ischaemia, and subsequent resuscitation with ambient air or 100% O2 . To investigate whether CO2 level during resuscitation influences myocardial damage. Design: Newborn piglets (12–36 hours) were exposed to hypoxaemia by ventilation with 8% O2 in nitrogen. When mean arterial blood pressure had fallen to 15 mm Hg, or base excess to < −20 mmol/l, the animals were randomly resuscitated by ventilation with either 21% O2 (group A, n = 29) or 100% O2 (group B, n = 29) for 30 minutes. Afterwards they were observed in ambient air for another 150 minutes. During resuscitation, the two groups were further divided into three subgroups with different CO2 levels. Analysis: Blood samples were analysed for cTnI, myoglobin, and creatine kinase-myocardial band (CK-MB) at baseline and at the end of the study. Results: cTnI increased more than 10-fold (p < 0.001) in all the groups. Myoglobin and CK-MB doubled in concentration. Conclusion: The considerable increase in cTnI indicates seriously affected myocardium. Reoxygenation with 100% oxygen offered no biochemical benefit over ambient air. CK-MB and myoglobin were not reliable markers of myocardial damage. Normoventilation tended to produce better myocardial outcome than hyperventilation or hypoventilation.